PENGARUH PENDEKATAN KONTEKSTUAL TERHADAP KETERAMPILAN MENULIS NARASI DALAM PEMBELAJARAN TEMATIK KELAS V SEKOLAH DASAR - Nurizky yarso; Siti Halidjah; Hery Kresnadi (Universitas Tanjungpura, 2019)
AbstractThis research aimns to analyse the influence of contextual approaches towards the narrative writing skills in the thematic learning of class V elementary school 35 south Pontianak. The research method used is the experimental method quasi research from experimental design.Experimental design that will be used in this study is a non equivalent control group design used two classes as the subject of research.The population in this study is all student of grade V elementary school 35 south Pontianak wich amounted to 96 students.The samples used in the study were VA graders the numbered 31 students as control and VC classes amounting to 35 students as experiment classes wuth random samling techiques.Data collection techniques used are measurement techniques and data collector tools is a written test of essay form.Data analysis results obtained an average pretest results of 66,71 and average posttest result of 74,59. Based on the result of the test-t calculation obtained tcount 4,073>t table 1,671,then H, received. This indicates that there are differences in the learning outcomes of the class students with experiment classes. Based on the results of the effect size is obtained bt ),75 which belongs to the medium criteria so that the contextual approach gives a moderate influence on narrative writing skills in the thematic learning of class V elementary school students Negeri 35 south Pontianak.Key words : Influence, Contextual Approach, Narrative Writing Skills Thematic.